Effects of using asphaltite as filler on mechanical properties of hot mix asphalt - Yılmaz, Mehmet; Kök, Baha Vural; Kuloğlu, Necati (My University, 2011)
This study focuses on determining the engineering characteristics of hot mix asphalt using mineral ?ller with asphaltite. Since asphaltite which consists of high amount of sulfur leads to air pollution when used as a heating material and also being hydrocarbon sourced, it seems better to use asphaltite in the hot mix asphalts. The hot mix asphalts in this study were prepared by using 25%, 50%, 75%, and 100% mixing ratios based on the mineral ?ller ratio to analyze the possibility of using asphaltite. The results reveal that using asphaltite as a whole ?ller signi?cantly increased the retained Marshall stability by 27% and increased the stiffness modulus by 91% at 15 .C. As for the tensile strength test, it was determined that the control mixtures lost 35% of its tensile strength ratio after one freeze–thaw cycle, however the mixtures containing completely asphaltite as ?ller lost only 13%. A remarkable increase was found at fatigue test. The cycle number leading to failure of the mixtures containing 25%, 50%, 75% and 100% asphaltite by weight of ?ller were 2.9, 3.6, 5.4 and 7.9 times greater than those of the control mixtures respectively at 300 kPa stress level. Using asphaltite as ?ller exhibited high performance by improving especially the resistance to moisture damage and fatigue life.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hot mix asphalt; Asphaltite; Moisture damage; Fatigue